Analisis Penyebab Demam Berdarah Dengue (DBD) Desa Bandar Klippa Kecamatan Percut Sei Tuan - Yusril Iza Mahendra; Azmi Ellah Syaniah; Rina Astari; T Zunita Miha Sy; Winda Aulia (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Dengue Hemorrhagic Fever or DBD really needs to be known by the public, where this disease is an infectious disease that can cause death. The causes of this disease really need to be known so that people are able to do prevention. Therefore, this article will analyze the causes of dengue hemorrhagic fever, especially in Bandar Klippa Village, Percut Sei Tuan District. The method used in this study is a qualitative descriptive method. The results of interviews and observations obtained are that the causes of dengue fever in Bandar Klippa Village are the lack of environmental cleanliness, imbalance of humidity, and the position of houses that are too close together. Then, prevention and control that can be done is to get used to living clean and healthy.